SMART PROTECTOR SCORING SYSTEM HAPKIDO - Berlian Chandra Kirana; Tiara Chandra Kirani; Himawan Wismanadi; Aghus Sifaq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the perceptions of middle-class consumers towards the ERIGO brand image in applying a low-key luxury strategy amid unstable economic conditions. Using a descriptive qualitative approach, data was collected through in-depth interviews with ten respondents who are consumers of ERIGO products. Using a thematic analysis method, the results show that purchasing decisions are influenced by material quality, product design, and competitive prices. Most respondents stated that ERIGO successfully conveyed an impression of low-key luxury through its simple yet elegant designs and high-quality materials. In addition, ERIGO was considered to offer a good balance between price and product quality. However, in unstable economic conditions, the majority of respondents prioritized their primary needs and considered purchasing ERIGO products based on their actual needs. These findings emphasize the importance of improving quality and brand communication strategies in order to maintain the loyalty of middle-class consumers in a competitive market.